Severity Index and Outcome of Hospitalized COVID-19 Patients in Capital Hospital, CDA, Islamabad - Aziz-un-Nisa , Lubna Meraj , Khizra Maqbool , Ifrah Ayaz , Anam Batool , Nadia Shams (Journal of Rawalpindi Medical College, 2021)
Objective: To assess clinical characteristics and outcome of patients with Covid-19 infection. Study design: Descriptive cross-sectional study. Place and duration of study: Department of Medicine, Capital Hospital Islamabad from February 01, 2021 to April 25, 2021. Methodology: A manual medical record of total of 221 patients was conducted, more than 18 years of age, both genders, who presented with features suggestive of Covid-19 infection were included. Patients were tested for COVID-19 PCR, blood complete picture and inflammatory markers. The data was analyzed by using SPSS version 42. Results: Among 221 patients, there were 125(56.6%) males and 96(43.4%) females. Mean age was 57.20+13.17 years. Total 155(70%) cases were Covid PCR +ve and 66(30%) –ve. 86(38.9%) cases had mild, 91(41.2%) had moderate and 44(19.9%) had severe covid-19 infection. Lymphopenia was observed in 154(69.7%) cases. C-reactive protein was positive in 178(80.5%) cases. Serum ferritin was raised in 114(51.5%) cases, D-dimers in 139(66.9%), lactic dehydrogenase in 167(75.5%) cases with significant association with disease severity. Serum interleukin, performed in moderate and severe cases only, had mean value of 54.1+105.94pg/ml. Diabetes mellitus was found significantly associated with mortality (p=0.007) as well as hypertension (p<0.0001). 207 cases were managed and discharged, 14 cases expired (6.33%). Mortality was significantly associated with disease severity (p<0.001). Remdesivir was given to symptomatic patients and 94.4 % patients were discharged vs 5.6 % expired. Remdesivir and tocilizumab was given in combination in severe/critical patients and 76.5% patients were discharged vs 23.5% expired. Conclusion: Covid-19 is a disease with variable presentations. Severity of Covid-19 infection is directly related to lymphopenia as well as inflammatory markers. IL-6 levels, raised in more severe cases, signify immune response to Covid-19. Disease is more severe in patients with comorbids. In moderate to severe disease remdesivir and in severe covid disease with high IL-6 levels combination of antiviral and tocilizumab may help to improve outcome.